The peacebuilding potential of technical and vocational education and training programmes in post-conflict Sierra Leone. Issue 1 (2nd January 2022) - van der Veen, Rikke; Datzberger, Simone
ABSTRACT: In peacebuilding contexts unemployed youth are frequently perceived as a high risk for the stability of a country while employed youth are seen as carrying an enormous potential for economic growth. This paper applies a social justice framework (4Rs) in analysing a Business Development (BD) programme that was implemented as part of Sierra Leone's Technical and Vocational Education and Training (TVET) strategy to promote entrepreneurship development and reduce unemployment among youth. Despite the BD programme's initial strengths, to recognize youth's heterogeneity with the aim to address some of the root causes of the war, we show how the programme struggled to counter social inequality, unemployment and neopatrimonialism. Sudden decreases in donor funding led to severe modifications of redistribution processes, thereby hampering youth's representation. This raises questions about the design of TVET strategies and BD programmes in post-conflict settings in general. Our paper further showcases how the resurfacing of the root causes of a conflict in the scope of small-scheme development programmes, can have far-reaching effects on young people's various relationships of trust, if not reconciliation process as a whole.